A case report of a family with developmental arrest of human prokaryotic stage zygote - Ma, Tianzhong; Zhou, Songxia; Xie, Xuezhen; Chen, Jingyao; Wang, Jing; Zhang, Guohong (Frontiers in Cell and Developmental Biology, 2024)
To study the genetic variation leading to the arrest phenotype of pronuclear (PN) zygotes. We recruited a family characterized by recurrent PN arrest during in vitro fertilization (IVF) and intracytoplasmic sperm injection cycles (ICSI) and performed whole-exome sequencing for 2 individuals. The transcriptome profiles of PN-arrest zygotes were assessed by single-cell RNA sequencing analysis. The variants were then validated by PCR amplification and Sanger sequencing in the affected individuals and other family members. A family characterized by recurrent PN arrest during IVF and ICSI cycles were enrolled after giving written informed consent. Peripheral blood samples were taken for DNA extraction. Three PN-arrest zygotes from patient III-3 were used for single-cell RNA-seq as described. This phenotype was reproduced after multiple cycles of egg retrieval and after trying different fertilization methods and multiple ovulation regimens. The mutant genes of whole exon sequencing were screened and verified. The missense variant c. C1630T (p.R544W) in RGS12 was responsible for a phenotype characterized by paternal transmission. RGS12 controls Ca2+ oscillation, which is required for oocyte activation after fertilization. Single-cell transcriptome profiling of PN-arrest zygotes revealed defective established translation, RNA processing and cell cycle, which explained the failure of complete oocyte activation. Furthermore, we identified proximal genes involved in Ca2+ oscillation–cytostatic factor–anaphase-promoting complex (Ca2+ oscillation–CSF–APC) signaling, including upregulated CaMKII, ORAI1, CDC20, and CDH1 and downregulated EMI1 and BUB3. The findings indicate abnormal spontaneous Ca2+ oscillations leading to oocytes with prolonged low CSF level and high APC level, which resulted in defective nuclear envelope breakdown and DNA replication. We have identified an RGS12 variant as the potential cause of female infertility characterized by arrest at the PN stage during multiple IVF and ICSI.